(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Within the framework of a research aiming to evaluate the impact of the use of Information and Communication Technologies (ICT) in higher teaching of physics, we carried out a study with 122 students enrolled in first year of the science spinneret of the physical matter (SMP) at the University Sidi Mohammed Ben Abdellah, Faculty of Sciences Dhar El Mahraz â€“ fez. This study aims in particular to identify the perceptions which these students have after learning the course of electricity integrating the ICT.The results of our investigation also show that the use of these toolsÂ in this course has provided an easy and convenient access toÂ its scientific content and improved the learning of 48.4% of the questioned students, in addition it allowed 52.5% of the surveyed students to actively participate and to ask more questions during the course. The results of our study have also shown that the teaching of the course of electricity within the university should be accompanied by a handout and based on more developed and detailed demonstrations in the board and a judicious use of the presentations integrating filmed experiments.